Pengaruh Artificial Intelligence (AI) dalam Evaluasi Pembelajaran Bahasa Indonesia pada Kalangan Mahasiswa - Muhammad Ryzki Tristianto; Aditya Syahban Nugraha; Adhika Ramdani; Adezian Santiago Nababan (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This article discusses the influence of Artificial Intelligence (AI) usage in the evaluation of Indonesian language learning among university students. The study explains that AI is used by students to help understand the material, improve assignments, and receive feedback more quickly. Using a descriptive quantitative approach, the article also explores students’ perceptions of the effectiveness of AI in supporting academic evaluation. It highlights ethical and technical challenges that arise, such as technological dependency and the low level of lecturer involvement in the use of AI. In addition to outlining key survey findings, the article provides an overview of the benefits, drawbacks, and potential of AI in enhancing the quality of educational evaluation.